Aspen Plus simulation of optimal biogas production in anaerobic digestion process - Ravendran, R. R.; Abdul Halim, Abdul Razik; Roziah, Zailan (IOP Publishing, 2019)
The demanding uses of fossil fuels and their associated environmental footprints are driving researches into renewable energy productions from organic resources and waste. Anaerobic digestion (AD) is an environment-friendly and cost-effective method to produce biogas from biomass. This biogas can be used in power generation, heating systems and in a combined heat and power (CHP) system. Nevertheless, biogas produced from AD contains a big fraction of CO2 and less methane purity. Aspen Plus simulation model was developed for the AD process to produce biogas, highlighting the economical potentials and environmental benefits. Four steps of AD including hydrolysis, acidogenesis, acetogenesis, and methanogenesis with eight reactions were simulated based on the respective stoichiometries. Optimization has involved the search to identify optimum feed flow rate and operating pressure to produce the maximum amount of pure methane. The obtained results showed that optimum feed rate was 0.36 l/day and operating pressure of 3 bar with hydrogen flow of 180 l/day. By using these optimum conditions, maximum amount of methane with high purity was achieved. Otherwise, through biomass natural decomposition, the methane would escape to the atmosphere as one of those significant greenhouse gases.